A study of Jewish identification and commitment in Johannesburg - Dubb, Allie A (Rhodes University, Faculty of Humanities, Department of Sociology, 1973)
The present study is an investigation of the nature and extent of Jewish identification and commitment in the Johannesburg Jewish Community. Jewish identification is defined as the attitudes and behaviour through which Jews express their identity with each other and with the Jewish group. It is conceived as comprising several dimensions - structural, cultural, religious, etc . - each of which may be assessed in terms of attitudes and/or behaviour. The aim of the study is, in the first place to describe the various dimensions of Jewish identification and to discover relations between them, and between them and other variables. Fieldwork consisted in the administration of a schedule, lasting about an hour, by trained interviewers to a quota sample of Johannesburg Jews. The schedule comprised questions relating to behaviour, attitudes and personal particulars. These data were augmented by several intensive interviews and by interviewers' observations. The final sample consisted of 286 men and women, in almost equal proportions, who had answered affirmatively the initial question, "Are you Jewish?" Five hypotheses were postulated, mainly on the basis of the findings of several previous studies in the United States. Briefly, it was postulated: firstly, that Jews would tend to identify through their attitudes to a greater extent than through actual behaviour; secondly that the area in which identification on the behavioural level was most likely to be manifested, was in patterns of social relations; thirdly, that observance of religious rituals was primarily a manifestation of identification rather than religious commitment ; fourthly; that there was some conflict between the desire to maintain the group and the feeling that barriers between ethnic groups should be minimal; and, finally , that the boundaries of the .Jewish community could be defined most adequately in terms of the relevance to community membership to the allocation of roles rather than in cultural terms. The first hypothesis had to be partially rejected; the remaining four were confirmed by the data. The study comprises eleven Chapters: in the first four, the problem is defined, hypotheses stated and research and sampling methods discussed; in Chapter Five, the demographic background is described, and in Chapters Six to Ten the findings relating to the various dimensions are presented and the hypotheses tested. In the final Chapter, the hypotheses and various specific findings are discussed in relation to their wider theoretical implications, as well as to their possibilities for further research and practical applications.
Keywords: Jews -- South Africa -- Johannesburg; Johannesburg (South Africa) -- Social conditions